The economic burden of HIV and type 2 diabetes comorbidity: Implications for care in countries with high burden of HIV - Sakhile K S Masuku; Joyce M Tsoka-Gwegweni; Ben Sartorius (Journal of Diabetology, 2019)
The economic burden of human immunodeficiency virus (HIV) and diabetes shows the need to design interventions to delay the development of type 2 diabetes in HIV-positive population. In 2015 alone, approximately US$19 billion was spent in the HIV/acquired immunodeficiency syndrome response in low- and middle-income countries. Approximately 57% of the total HIV resources in low- and middle-income countries come from the local government budgets. Rising numbers of new HIV infections in many countries mean that US$26.2 billion will be required for the response to the epidemic in 2020. On the other hand, the cost of diabetes mellitus alone is projected to be US$745 billion by 2030 and approximately US$300 billion is estimated to be the cost incurred in low- and middle-income countries. People diagnosed with diabetes at the age of 40 years spent US$124,600 more than those without diabetes over their remaining lifetime. The co-occurrence of type 2 diabetes and HIV increases the economic burden at patient and country level, hence there is a need to identify interventions for preventing diabetes among people living with HIV. This review has shown that both lifestyle and pharmacologic interventions are proven effective and cost-effective. Lifestyle modification, metformin intervention, and diabetes surveillance among people living with HIV are cost-effective strategies that can effectively prevent the development of diabetes in this population. There is also a need for the health policy to support the implementation of these strategies. Health and social policies should support the funding of intensive lifestyle and metformin interventions for diabetes prevention in high-risk groups.